Nigeria National Policies and Strategies (NPS) Capacity-Sharing Workshops Series: Introduction to Social Accounting Matrices (SAM) - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2022)
The International Food Policy Research Institute (IFPRI) hosted the first in a series of capacity-sharing workshops under the CGIAR National Policies and Strategies for Food, Land and Water Systems Transformation (NPS) Initiative1 on July 7, 2022. The training, which included government, policy think tanks, and other stakeholders introduced the social accounting matrix (SAM) as a policy and investment tool for economy-wide analysis and transformation.